If f(x) = 1/4x+2 and g(x) = −3x^2+2.
determine the value of -3g(1)
and determine the value of f^-1(1)
please help me with this
3 answers
can someone please help me with that answer?^
just plug and chug
-3g(1) = -3(-3*1^2+2) = -3(-3+2) = 3
On the other, what you have typed is ambiguous.
If y = 1/(4x) + 2 then x = 1/(4y-8)
If y = 1/4 x + 2 then x = 4(y-2)
if y = 1/(4x+2) then (1/y - 2)/4 = 1/(4y) - 1/2
-3g(1) = -3(-3*1^2+2) = -3(-3+2) = 3
On the other, what you have typed is ambiguous.
If y = 1/(4x) + 2 then x = 1/(4y-8)
If y = 1/4 x + 2 then x = 4(y-2)
if y = 1/(4x+2) then (1/y - 2)/4 = 1/(4y) - 1/2
thank you so much this really helped